Álvaro Cepeda Samudio, Obra Literaria, edizione critica di Fabio Rodríguez Amaya e Jacques Gilard (Altre Modernità, 2017)
Álvaro Cepeda Samudio, Obra Literaria, edizione critica di Fabio Rodríguez Amaya e Jacques Gilard